2015
DOI: 10.1007/s10096-015-2428-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct molecular versus culture-based assessment of Gram-positive cocci in biopsies of patients with major abscesses and diabetic foot infections

Abstract: Major abscesses and diabetic foot infections (DFIs) are predominant subtypes of complicated skin and skin structure infections (cSSSIs), and are mainly caused by Staphylococcus aureus and β-hemolytic streptococci. This study evaluates the potential benefit of direct pathogen-specific real-time polymerase chain reaction (PCR) assays in the identification of causative organisms of cSSSIs. One-hundred and fifty major abscess and 128 DFI biopsy samples were collected and microbial DNA was extracted by using the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…PCR revealed pathogens that had not been recognized by culture-methods such as MRSA species. Previous research reveals a higher specificity for culture tests when compared to RT-PCR as a reference while a lower sensitivity, a slightly higher PPV and a higher NPV [8]. Similar to this earlier study, RT-PCR revealed more S. aureus than identified through culture-methods [8].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…PCR revealed pathogens that had not been recognized by culture-methods such as MRSA species. Previous research reveals a higher specificity for culture tests when compared to RT-PCR as a reference while a lower sensitivity, a slightly higher PPV and a higher NPV [8]. Similar to this earlier study, RT-PCR revealed more S. aureus than identified through culture-methods [8].…”
Section: Discussionsupporting
confidence: 82%
“…However, more accurate tests should be explored since culture-based methods have been reported to have a high number of false-negatives [8]. In the present study, molecular tests were more sensitive but less specific than culture-based methods.…”
Section: Discussionmentioning
confidence: 60%
“…ST80 is the main PVL clone circulating in Europe and North Africa [ 147 , 148 , 149 ]. Rates of PVL-producing clones in DFI remain low in comparison to data concerning SSTIs [ 127 ] (e.g., the epidemic furuncles (42%), major abscesses (73%) and gold surgically-drained abscesses (89%)) [ 146 , 150 , 151 , 152 ]. Indeed, in DFI, a higher incidence of PVL-positive isolates among subjects with CA-MRSA could be observed (31.8% versus 5.7%; p = 0.004) [ 153 ].…”
Section: Staphylococcus Aureus Toxins In Dfismentioning
confidence: 88%
“…The PVL-producing clones were rarely isolated from DFI ( Table 2 ) [ 48 , 110 , 122 , 144 , 145 ]. However, this prevalence varies between countries: France (~3%), Algeria and The Netherlands (~14%) [ 48 , 146 ]. The main PVL-producing strains isolated from DFI belong to ST80-MRSA (14/21 strains), followed by ST152 (6/21) and CC30 (1/21).…”
Section: Staphylococcus Aureus Toxins In Dfismentioning
confidence: 99%
“…In addition, the elevated contents of carbohydrates and proteins in the exudates of injured soft tissues are beneficial to the survival and reproduction of bacteria, which extremely easily trigger soft tissue infection in the extremity, especially the feet ( 7 , 8 ). Large number of studies have demonstrated that the pathogens of infection are dominated by Gram-negative bacteria possessing strong drug resistance ( 9 ). Defects of the soft tissue in the extremity of DF patients heal more slowly than those in other parts because they are located far away from the heart and have less collateral circulation and blood supply than other parts.…”
Section: Discussionmentioning
confidence: 99%